2022
DOI: 10.1111/jav.02866
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction delays breeding and affects insulin‐like growth factor‐1, oxidative damage and haematocrit value before egg‐laying in female canaries

Abstract: Environmental challenges, such as fluctuations in food availability, could influence reproductive investment. If resource availability is poor, individuals need to decide in which life‐history process they invest more energy and vital compounds, which determine the cost of reproduction. In resource allocation, the physiological pathways have important roles. The aim of our study was to examine whether food availability influenced physiological traits (insulin‐like growth factor‐1 (IGF‐1) concentration, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(137 reference statements)
1
2
0
Order By: Relevance
“…However, another study on broiler chicken found that food restriction resulted in higher IGF-1 levels than controls throughout the study (from 15 to 28 weeks of age) (Hocking et al, 2007). We also found that female canaries responded to food restriction by increasing IGF-1 levels during breeding (Hargitai et al, 2022). These studies only analyzed the overall response to food-restriction, but here we show that within a single population, individuals may differ markedly in their physiological response to changes in nutritional conditions.…”
Section: Discussionsupporting
confidence: 57%
“…However, another study on broiler chicken found that food restriction resulted in higher IGF-1 levels than controls throughout the study (from 15 to 28 weeks of age) (Hocking et al, 2007). We also found that female canaries responded to food restriction by increasing IGF-1 levels during breeding (Hargitai et al, 2022). These studies only analyzed the overall response to food-restriction, but here we show that within a single population, individuals may differ markedly in their physiological response to changes in nutritional conditions.…”
Section: Discussionsupporting
confidence: 57%
“…It has been also reported that IGF1 increases the expression of genes involved in steroidogenesis in avian preovulatory follicles, which improves egg production (Francoeur et al., 2023). Contrarily, DR during the pre‐laying period increased circulating IGF‐1 levels in domesticated canaries, but did not have a significant effect on egg quality traits (Hargitai et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the physiological response to dietary restriction may vary among avian species. For instance, we previously found that DR decreased liver IGF1 gene expression in male and female Japanese quails ( Coturnix japonica ) (Reda, Ndunguru, Csernus, Knop, Lugata, et al., 2024), whereas other studies have reported that DR increased plasma IGF‐1 in female canaries ( Serinus canaria ) (Hargitai et al., 2022), broiler chicken hens (Hocking et al., 1994) and male and female bearded reedlings ( Panurus biarmicus ) (Tóth et al., 2022). These mixed results indicate that, based on the existing evidence, it is difficult to draw a general conclusion about how changes in food availability affect the IGF‐1 system.…”
Section: Introductionmentioning
confidence: 89%